Parody of political correctness or allegory of “Immaterial Labour”? A second look at Francis Veber’s Le Placard (2001) - Lane, Jeremy F. (Sage, 2015)
This article questions whether readings of Francis Veber’s Le Placard (2001) as simply a parody of political correctness have tended to overlook the allegorical significance of its depiction of a middle-aged executive forced to pretend to be gay, simulating libidinal investments he does not in fact possess, in order to protect his job. It argues that the film merits re-interpretation as being not only a parody of political correctness but also a powerful allegory for the increasing demands placed on employees to invest their most personal affects and aptitudes in their work. Drawing on the work of Yann Moulier Boutang, the article interprets such demands as symptomatic of a regime of ‘cognitive capitalism’, in which ‘immaterial’ forms of labour represent the primary source of surplus value. The article thus offers an alternative reading of the film’s treatment of questions of work, gender, sexuality, family, and nation, before situating Le Placard in the context of a broader range of recent French filmic representations of the contemporary workplace.